Experiencing rondo form by integrating elementary music methodologies and theories - Aadalen, Kelsey (Kansas State University, 2020)
Notable elementary music methodologies and theories are comprised of Kodály, Dalcroze, Orff, and Gordon. By implementing and integrating elements from these four influential methods, my lesson plan focuses on Kansas’ state standards of performing, creating, and responding to music while learning about rondo form. While my undergraduate work taught me what to teach, my graduate work at Kansas State has taught me how and why, greatly developing and evolving my teaching. Prior to my graduate classes, the curriculum I compiled was exciting and stimulating, but random. I favored certain concepts and state standards with which I was more comfortable. In my coursework, I learned how students’ minds work and how to reach more of them, how to vertically align my lessons between units and multiple grade levels, and how to expand my personal comfort zone to encompass a diverse and more relevant pedagogy so each and every unique student is engaged and successful. To demonstrate these major developments, my video teaching lesson plan centers on part of a complete unit I made for MUSIC 809 where I worked on proper sequencing of activities and lessons inspired by Kodály, Dalcroze, Orff, and Gordon. The video recording of this lesson will show the first time I tried multiple elements like whole-part-whole singing instruction and improvising a simple piano accompaniment while the students improvised an unpitched percussion section.
Keywords: Kodaly; Orff; Gordon; Dalcroze; Rondo form; Music philosophy